Croatian twin study of body mass index and physical activity - Vukasović, Tena (Array, 2012)
Earlier studies have established that a substantial percentage of variance in obesity-related phenotypes and in exercise behaviors is influenced by genetic and environmental effects. Heritability estimates from different countries range between 65 and 85% for body mass index (BMI), while this percentage is somewhat lower for exercise behavior (35-55%). The aim of this study was to explore the relationship between BMI and physical activity in a sample of Croatian twins. Data on BMI and physical activity (frequency and intensity) were collected from 339 twin pairs (105 MZ and 234 DZ) aged between 15 and 22 years. Heritability estimates from our study are in line with those obtained in previous studies indicating that genetic factors contribute around 80% to individual differences in BMI, around 60% for the frequency of physical activity (FPA) and around 50% for the intensity of physical activity (IPA). Bivariate analyses indicate that there is a positive genetic (rA=.21) and a negative non-shared environmental correlation (rE=-.34) between FPA and BMI, meaning that the same genetic factors contributing to higher FPA also contribute to higher BMI. On the other hand, same non-shared environmental factors contributing to higher FPA also contribute to lower BMI. Genetic and non-shared environmental correlations between BMI and IPA were not statistically significant.